2017
DOI: 10.1080/09286586.2016.1259639
|View full text |Cite
|
Sign up to set email alerts
|

The National Eye Survey of Trinidad and Tobago (NESTT): Rationale, Objectives and Methodology

Abstract: Purpose: This paper describes the rationale, study design and procedures of the National Eye Survey of Trinidad and Tobago (NESTT). The main objective of this survey is to obtain prevalence estimates of vision impairment and blindness for planning and policy development. Methods: A population-based, cross-sectional survey was undertaken using random multistage cluster sampling, with probability-proportionate-to-size methods. Eligible participants aged 5 years and older were sampled from the non-institutional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…7 A recently conducted National Eye Study of Trinidad and Tobago (NESTT) reported blindness prevalence of 0.73% and moderate to severe visual impairment (MVI) of 5.34% in adults above 40 years of age. 8 , 9 The major causes of blindness were reported to be glaucoma (28.6%) and cataract (25.7%), followed by diabetic retinopathy (11.4%). The major causes of moderate to severe visual impairment were uncorrected refractive error (44.0%) and cataract (30.1%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 A recently conducted National Eye Study of Trinidad and Tobago (NESTT) reported blindness prevalence of 0.73% and moderate to severe visual impairment (MVI) of 5.34% in adults above 40 years of age. 8 , 9 The major causes of blindness were reported to be glaucoma (28.6%) and cataract (25.7%), followed by diabetic retinopathy (11.4%). The major causes of moderate to severe visual impairment were uncorrected refractive error (44.0%) and cataract (30.1%).…”
mentioning
confidence: 99%
“…The major causes of moderate to severe visual impairment were uncorrected refractive error (44.0%) and cataract (30.1%). 8 , 9 …”
mentioning
confidence: 99%
“…With aging, organ function deteriorates and the incidence of visual impairment among the older adults increases. 26 It has been reported that visual impairment has an impact on the physical and mental health of the older adults, 27 including depression and reduced life satisfaction, affecting participation in social activities and independent ADL. Interestingly, a previous study 8 on SA also explored the impact of visual ability, but the effect was not strong, possibly because of different evaluation criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our sincere thanks to everyone in the National Eye Survey of Trinidad and Tobago Study Group. 2…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Details are provided elsewhere. 2 Briefly, we sampled 9913 eligible people aged >5 years, including 4263 aged >40 years, residing in 3556 households (95.9% coverage) in 120 clusters, using multi-stage, random cluster sampling with probability-proportional-to-size methods. We measured presenting distance and near visual acuity outside households, using Logarithm of the Minimum Angle of Resolution (LogMAR) charts at 3m and 40cm, respectively, and standardized protocols (Stage 1).…”
mentioning
confidence: 99%